2016
DOI: 10.1038/srep34257
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cell surface area and deformability of individual human red blood cells over blood storage using quantitative phase imaging

Abstract: The functionality and viability of stored human red blood cells (RBCs) is an important clinical issue in transfusions. To systematically investigate changes in stored whole blood, the hematological properties of individual RBCs were quantified in blood samples stored for various periods with and without a preservation solution called citrate phosphate dextrose adenine-1 (CPDA-1). With 3-D quantitative phase imaging techniques, the optical measurements for 3-D refractive index (RI) distributions and membrane fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 66 publications
4
61
0
1
Order By: Relevance
“…Three-dimensional refractive index tomograms (37) and digital holographic microscopy images (38) have been used to measure temporal changes in morphological parameters of stored RBCs (39,40). Three-dimensional refractive index tomograms (37) and digital holographic microscopy images (38) have been used to measure temporal changes in morphological parameters of stored RBCs (39,40).…”
Section: Comparative Analysismentioning
confidence: 99%
“…Three-dimensional refractive index tomograms (37) and digital holographic microscopy images (38) have been used to measure temporal changes in morphological parameters of stored RBCs (39,40). Three-dimensional refractive index tomograms (37) and digital holographic microscopy images (38) have been used to measure temporal changes in morphological parameters of stored RBCs (39,40).…”
Section: Comparative Analysismentioning
confidence: 99%
“…QPI is based on the determination of optical path length changes that can be acquired with minimum efforts of sample preparation. Moreover, hemoglobin mass changes of red blood cells were proposed as parameters to quantify cell quality during storing (12) and image processing based methods were demonstrated to be capable to distinguish between different types of blood cells (13,14). Moreover, quantitative phase imaging allows the extraction of absolute biophysical parameters like volume, refractive index, and dry mass of suspended cells that are related to various cellular features and processes (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 87%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%